WISATA HALAL, APAKAH HANYA SEBAGAI JARGON DI INDONESIA ? - Faisal Yusni Nuralamsyah (Tulisan Ilmiah Pariwisata (TULIP), 2020)
This research was conducted to examine about halal tourism in Indonesia that is still cursory jargon alone, because there are still misinterpretations and halal tourism concepts have not been done correctly. For this study the authors used literacy study method by collecting evidence based on existing literacy balanced with data collected based on observation and supporting data collection. In this study, the authors still think that halal tourism in Indonesia is jargon because of the unavailability of regulation, certification of halal tourism that does not exist, human resources (HR) that are not adequate enough and other supporting infrastructure that is still quite lacking.